The state of readiness of future teachers-psychologists to work with children with attention deficit hyperactivity disorder (The Journal of Psychology and Sociology, 2025)
The article explores how future educational psychologists are trained to work with children, who have emotional and behavioral difficulties, particularly ADHD. The authors discuss the phenomenon of hyperactive in the context of modern society and describe the real challenges faced by parents and teachers of such children.  The paper also highlights international approaches to training psychologists, drawing on examples from the United States and several European countries. The main aim of study is to asses how well today is psychology students are prepared to support children with ADHD. Based on these findings, the authors propose practical steps for improving training programs so that graduates can work with these children more effectively.The study emphasizes the importance of quality training for specialists to effectively work with children experiencing emotional-volitional disturbances and offers ways to optimize the educational process, taking into account the specific needs of this category of children.The practical value of this work lies in identifying what already functions well in the training of psychologists who support children with ADHD, and what still needs to be improved. Based on this analysis, the authors suggest specific steps for updating the training programs. Putting these measures into practice should help specialists work with such children more effectively and make their integration into school everyday life easier.As a result of the research, it becomes possible to develop high-quality skills and competencies for specialists working with children with ADHD and to improve the quality of their training.Keywords: teacher-psychologist, children with attention deficit and hyperactivity, training of teacher-psychologists, educational program, research.